Mosquitoes: how to manage them around your home - Hofsteen, L. M., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes how to control mosquitoes around your home.
CEPEP 6/03, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Mosquitoes -- Control; Pesticides -- Environmental aspects